Pengembangan media pembelajaran kartematika berbasis aplikasi android untuk meningkatkan kemampuan pemahaman matematis siswa pada materi koordinat kartesius - Nengsih, Sri Dewi; Solfitri, Titi; Maimunah (Karoteh Utama, 2024)
Students' mathematical understanding ability is often low, particularly on the Cartesian coordinate material, due to the lack of innovative learning media used in schools. This study aims to develop Kartematika, an Android-based learning media that is valid and practical for facilitating students' mathematical understanding. The research employs the 4-D development model, which includes the stages of Define, Design, Develop, and Disseminate. Data collection instruments include validation sheets and student response questionnaires, while data analysis techniques involve validity and practicality tests. Validation results show that the learning media achieved a validity level of 93.6%, categorized as highly valid. Practicality tests were conducted in two stages, yielding results of 91.4% (highly practical) in a small group trial and 89.6% (highly practical) in a large group trial. Based on the findings, the Android-based Kartematika learning media meets the criteria of validity and practicality, making it suitable for improving students' mathematical understanding on Cartesian coordinate material. This media is expected to serve as an innovative solution for mathematics learning in schools.